Field-Scale Evaluation of Biosolids-Derived Organomineral Fertilisers Applied to Ryegrass (Lolium perenne L.) in England - Diogenes L. Antille; Ruben Sakrabani; Richard J. Godwin (Applied and Environmental Soil Science)
A field-scale experiment was conducted to compare the suitability of two organomineral fertiliser (OMF) formulations (OMF10—10 : 4 : 4 and OMF15—15 : 4 : 4) with urea and biosolids granules applied to perennial ryegrass. Results showed a 25% to 30% increase in dry matter yield (DMY) with application of OMF compared with biosolids granules but about 5% lower than urea. For OMF, an average input of yielded which was similar to that of urea; whereas, for biosolids, a yield of required an input of but DMY was lower (). Agronomic efficiencies with OMF were in the range of 26 to 35 kg , approximately double those of biosolids but about 5% to 10% lower than urea. Soil extractable P levels remained close to constant; therefore, soil P Index was not affected by OMF application. This result supported the reasons for the proposed OMF formulations and demonstrated the advantage of the products compared with biosolids which induced an increase (), in soil extractable P. The application of OMF at rates which do not exceed the optimum N rate for the grass crop should not induce significant changes in soil P Index including application to soils with satisfactory P levels. OMF application strategies are discussed which will enable minimising environmental concerns and maximising fertiliser use efficiency.